Spatial Model of Deforestation in Kalimantan from 2000 to 2013 - Judin Purwanto; Teddy Rusolono; Lilik Budi Prasetyo (Institut Pertanian Bogor (IPB University), 2015)
Forestry sector is the biggest carbon emission contributor in Indonesia which is mainly caused by deforestation. In Kalimantan island one of the largest island in Indonesia has a significant area of forest cover still can be found although an alarming rates deforestation is also exist. This study was purposed to established spatial model of deforestation in Kalimantan island. This information is expected to provide options to develop sustainable forest management in Kalimantan trought optimizing environment and socio-economic purposes. This study used time-series land cover data from the Ministry of Environment and Forestry (2000 – 2013) and is validated by SPOT 5/6 images in 2013. The spatial model of deforestation were developed using binary logistic. The results of logistic regression analysis obtained spatial model of deforestation in Kalimantan = 1.1480714 – (0.033262*slope) – (0.002242*elevation) – (0.000413*distance from forest edge) + (0.000045*Gross Regional Domestic Product). Validation test showed overall accuracy about 79.64% and 77.01% for models of deforestation in 2000–2006 and 2006–2013 respectively.